Chlorhexidine to treat oral mucositis in patients with acute leukemia: systematic review - Macedo,Rômulo Augusto de Paiva (2015)
ABSTRACT BACKGROUND AND OBJECTIVES: Leukemias impair hematopoietic stem-cells shunting and promote a proliferation of malignant cells without functional competence. Studies point that oral manifestations such as pain, hyperplasia and gum bleeding may be one of the first signs in leukemia patients. In light of the above, this study aimed at carrying out a systematic analysis of articles published in the last 15 years, with regard to chlorhexidine to treat and prevent mucositis in acute leukemia children under chemotherapy. CONTENTS: A systematic search of articles published between January 2000 and January 2015 was carried out in Pubmed/Medline, Science Direct and LILACS databases. After systematic search, 6 articles have fulfilled all methodological inclusion criteria. Chlorhexidine is an important means of preventing and treating oral mucositis and studies refer that 0.12% chlorhexidine gluconate effectiveness is probably related to its bactericide action. Adequate oral hygiene is important to prevent mucositis and other therapeutic modalities have shown to be effective to treat and prevent oral mucositis. CONCLUSION: Chlorhexidine gluconate does not totally eliminate oral mucosa injuries, but is able to decrease their frequency and intensity without significant noxious effects. However, other drugs compared to chlorhexidine in this study may present better results.